La0.7Sr0.3MnO3 nanoparticles coated with fatty amine - Rajagopal, Rajashree; Mona, J.; Kale, Sangeeta N.; Bala, Tanushree; Pasricha, Rem; Poddar, P.; Sastry, M.; Bhagavatula L. V. Prasad; Kundaliya, Darshan C.; Ogale, S. B. (Applied Physics Letters, 2006)
We report on the synthesis of La0.7Sr0.3MnO3 (LSMO) nanoparticles having perovskite structure and particle size of the order of 30 rim. The process involves citrate-gel synthesis, size filtering, and; surface coating with a shell of octadecyl amine (ODA) using electrostatic interaction-assisted novel chemical route. Magnetic measurements show the Curie temperature of similar to 360 K establishing the desired stoichiometry and phase. Fourier transform infrared-studies bring out. that the amine group of ODA interacts with the LSMO surface. Refluidization yields uniform redispersion of the coated and dried powder. (c) 2006 American Institute of Physics.

Blocking effects in irreversible adsorption of linear macromolecules - Shelke, Pradip B.; Banpurkar, Arun G.; Ogale, S. B.; Limaye, A. V. (Surface Science, 2007)
{A new variant of random sequential adsorption (RSA), namely random sequential ballistic adsorption (RSBA), is proposed to explore the possible role of blocking effects in the adsorption dynamics of ballistically arriving objects. These objects upon adsorption can protrude outside the substrate and in turn can obstruct and hence reject the adsorption of newly arriving objects. Adsorption of linear macromolecules (modeled as infinitesimally thin needles), on a two-dimensional continuum substrate is studied using RSBA model. It is shown analytically that in late time regime, the number n(t) of adsorbed objects at time t follows a power law n(t) similar to t(alpha), as in RSA, but with a different exponent
Keywords: Adsorption; adsorption kinetics; Monte Carlo simulations; random sequential adsorption (RSA)

Au-ZnO: a tunable localized surface plasmonic nanocomposite - Mishra, Y. K.; Mohapatra, S.; Singhal, R.; Avasthi, D. K.; Agarwal, Dinesh C.; Ogale, S. B. (Applied Physics Letters, 2008)
In this letter, we report the thermal processing controlled tunability of localized surface plasmon resonance (LSPR) of Au nanoparticles embedded in ZnO matrix. Au-ZnO nanocomposite films were prepared by atom beam cosputtering and were annealed from 200 to 600 degrees C in Ar. A regular redshift similar to 110 nm (from 505 to 615 nm) in LSPR peak with increase in annealing temperature up to 600 degrees C is observed. Transmission electron microscopy results confirm the formation of Au nanoparticles supported by ZnO nanorods at annealing temperature of 600 degrees C. The Au-ZnO nanocomposite exhibits significant enhancement in the Raman signal for C(70) molecules. (C) 2008 American Institute of Physics.

Hydrazine based facile synthesis and ordered assembly of metal nanoparticles (Au, Ag) on a bacterial surface layer protein template - Puranik, Sarang S.; Joshi, Hrushikesh M.; Ogale, S. B.; Paknikar, K. M. (Journal of Nanoscience and Nanotechnology, 2008)
An efficient and facile procedure is developed for concurrent in situ synthesis and ordered assembly of metal nanoparticles on a periodic two dimensional protein array. The S-layer protein of Bacillus subtilis exhibiting uniform pore size is used as template. Synthesis of gold and silver nanoparticles anchoring on the pores of S-layer is achieved by chemical reduction of respective metal salt laden protein template. Transmission electron microscopy reveals formation of well ordered and separated gold and silver nanoparticles with an average diameter of 6 +/- 1 nm and 4 +/- 1 nm, respectively. The periodic arrangement of nanoparticles is dictated by the native structure of S-layer protein array as the nanoparticle locations are found to be correlated to the nanosized pores of the crystalline S-layer array.
Keywords: Bacteria; Metal Nanoparticles; synthesis

Liquid-phase synthesized mesoporous electrochemical supercapacitors of nickel hydroxide - Chang, Jinho; Park, Mira; Ham, Dukho; Ogale, S. B.; Mane, Rajaram S.; Han, Sung-Hwan (Electrochimica Acta, 2008)
Electrochemical supercapacitive (ES) properties of liquid-phase synthesized mesoporous (pore size distribution centered similar to 12 nm) and of 120 m(2)/g surface area nickel hydroxide film electrodes onto tin-doped indium oxide substrate are discussed. The amounts of inner and outer charges are calculated to investigate the contribution of mesoporous structure on charge storage where relatively higher contribution of inner charge infers good ion diffusion into matrix of nickel hydroxide. Effect of different electrolytes, electrolyte concentrations, deposit mass and scan rates on the current-voltage profile in terms of the shape and enclosed area is investigated. Specific capacitance of similar to 85 F/g at a constant current density of 0.03 A/g is obtained from the discharge curve. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: electrochemical supercapacitors; mesoporous structure; nickel hydroxide

Peculiarities of the adsorption kinetics of mixed convex plus concave contour objects - Shelke, Pradip B.; Ogale, S. B.; Khandkar, M. D.; Limaye, A. V. (Physical Review E, 2008)
Random sequential adsorption of mixed convex plus concave contour (MC) objects exhibits some distinctly different peculiar characteristics than the cases of purely convex objects. Though the substrate coverage approaches the jamming limit with time t as t(-p), same as that for convex objects, the law p similar to 1/d(f), valid for convex objects with d(f) degrees of freedom, does not hold for MC objects. Interestingly, for a fixed number of degrees of freedom, the exponent p changes with the degree of nonconvexity and bears a near perfect correlation with the same.

On the change in bacterial size and magnetosome features for magnetospirillum magnetotacticum (MS-1) under high concentrations of zinc and nickel - Kundu, S.; Kale, A. A.; Banpurkar, Arun G.; Kulkarni, G. R.; Ogale, S. B. (Biomaterials, 2009)
The characteristic size, shape and specific alignment of magnetite crystals synthesized by magnetotactic bacteria is a highly coordinated process with precise control over magnetosome vesicle formation, uptake and transport of Fe, and magnetite biomineralization. Magnetosome membranes along with some specific membrane proteins regulate crystal nucleation and morphology of magnetite. Several previous works have indicated that the morphology of mature magnetite crystals is largely unaffected by environmental conditions, though some recent studies have shown the possibility of manipulation of the biomineralization process. In this study we have examined the effects of high concentrations of Zinc and Nickel on the growth of Magnetospirillum magnetotacticum (MS-1) and the corresponding magnetosome formation. Using various characterizations it is shown that the growth of the bacterial cells, as well as the size, shape and magnetosome chain alignment is significantly influenced in the presence of high concentrations of Zn or Ni. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Biomineralization; magnetite; Magnetosome; Magnetospirillum magnetotacticum; Nickel; zinc

VLS-like growth and characterizations of dense ZnO nanorods grown by e-beam process - Agarwal, Dinesh C.; Chauhan, R. S.; Avasthi, D. K.; Sulania, I.; Kabiraj, D.; Thakur, P.; Chae, K. H.; Chawla, Amit; Chandra, Ramesh; Ogale, S. B.; Pellegrini, G.; Mazzoldi, P. (Journal of Physics D-Applied Physics, 2009)
We present a new approach to produce ZnO nanorods in a reproducible manner at a temperature lower than other physical vapour deposition techniques, such as the vapour-liquid-solid mechanism. Arrays of well-aligned ZnO nanorods of uniform diameter have been synthesized on the Si substrate precoated with Au, using a simple electron beam evaporation method without the flow of any carrier gas. Scanning electron microscopy and atomic force microscopy characterizations show that as-grown nanorods are well aligned and uniform in diameter. X-ray diffraction measurements and clear lattice fringes in high-resolution transmission electron microscopy image show the growth of good quality polycrystalline hexagonal ZnO nanorods and a < 0 0 2 > growth direction. The polarization-dependent studies of near edge x-ray absorption fine structure (NEXAFS) are performed to investigate the electronic structure of the zinc and oxygen ions. The analysis of NEXAFS spectra at different angles of incidence of photon flux indicates the formation of ZnO nanorods having anisotropic behaviour of O and Zn states. The photoluminescence spectrum exhibits strong ultraviolet emission at 385 nm and the UV-visible spectrum also shows a band-gap transition around 390 nm indicating the good quality of nanorods. The catalytic growth mechanism of the ZnO nanorods is discussed on the basis of experimental results in this work.

Controlling stoichiometry in low temperature synthesis of La0.7Sr0.3MnO3 nanoparticles - Azarifar, Ali; Yadav, P. A.; Chawla, A. K.; Jog, Jyoti Prakash; Patil, S. I.; Chandra, Ramesh; Ogale, S. B. (Advanced Science Letters, 2011)
Nanoparticles of complex oxides (<20 nm) are desirable for several applications in view of the diverse range of physical properties of such oxides. However the simultaneous presence of multiple cation precursors makes the corresponding chemical synthesis non-trivial with possible intermediate evolution of secondary phases. Such phases could react at high temperatures to form the desired stoichiometry, but this process is diffusion limited and can lead to larger particles. In this work we examine the role of three different reaction and growth controlling additives, namely dextran, citric acid and hexamine, on the synthesis of the well known colossal magneto-resistive (CMR) manganite La0.7Sr0.3MnO3. We demonstrate that phase evolutions differ significantly in the three cases, and the physical properties of the products also differ dramatically. Only dextran is shown to yield the desired phase with faceted nanoparticles at as low a temperature as 600 degrees C. A high saturation moment of similar to 47 emu/gm is realized at 10 K with a good square hysteresis loop. In 650 degrees C annealed sample, room temperature magnetization of similar to 15 emu/gm was obtained, which brings the nanoparticles in the applicability domain.
Keywords: Citric acid; Complex Oxide; Dextran; Hexamine; hydrothermal

From small aromatic molecules to functional nanostructured carbon by pulsed laser-induced photochemical stitching - Gokhale, R. R.; Thakare, V. P.; Warule, S.; Lefez, Benoit; Hannoyer, Beatrice; Jog, Jyoti Prakash; Ogale, S. B. (AIP Advances, 2012)
A novel route employing UV laser pulses (KrF Excimer, 248 nm) to cleave small aromatic molecules and stitch the generated free radicals into functional nanostructured forms of carbon is introduced. The process differs distinctly from any strategies wherein the aromatic rings are broken in the primary process. It is demonstrated that this pulsed laser-induced photochemical stitching (PLPS) process when applied to routine laboratory solvents (or toxic chemical wastes when discarded) Chlorobenzene and o-Dichlorobenzene yields Carbon Nanospheres (CNSs) comprising of graphene-like sheets assembled in onion-like configurations. This room temperature process implemented under normal laboratory conditions is versatile and clearly applicable to the whole family of haloaromatic compounds without and with additions of precursors or other nanomaterials. We further bring out its applicability for synthesis of metal-oxide based carbon nanocomposites. Copyright 2012 Author(s). This article is distributed under a Creative Commons Attribution 3.0 Unported License. [http://dx.doi.org/10.1063/1.4721268]